Clinical semiology of temporal lobe seizures in preschool children: contribution of invasive recording to anatomical classification. Issue 4 (17th August 2021) - Fohlen, Martine; Taussig, Delphine; Ferrand‐Sorbets, Sarah; Chipaux, Mathilde; Dorfmuller, Georg
Abstract: Objective : Focal seizure semiology is often inadequately studied, specifically in preschool children. Among drug‐resistant epilepsies amenable to surgery, temporal lobe seizure semiology has been widely described in this age group. Nevertheless, a systematic anatomo‐electroclinical study has never been performed. Methods : We retrospectively reviewed the charts of patients younger than six years old at the time of video‐EEG recording who were operated on for temporal lobe epilepsy in our centre between 2010 and 2016. In order to describe the electroclinical semiology and establish anatomo‐clinical correlations, we reviewed all the recorded seizures on scalp and invasive video‐EEG and analysed pre‐ and postsurgical clinical data, MRI scans, and surgical and pathological data. We classified patients into the following four anatomical groups: mesio‐temporal, temporal lateral, polar, and mesio‐lateral, and for each group we selected video‐EEG samples for educational purposes. Results : Twenty‐eight patients fulfilled the selection criteria. Twenty‐three patients (82%) were explored with invasive electrodes that consisted of foramen ovale electrodes in 11 (39%) and stereoelectroencephalography in 12 (43%). The majority of the 53% of patients with mesio‐temporal epilepsies had specific ictal semiology, as described in adults. The others had subtle seizures or seizures limited to apnoea. The other groups also had some features comparable to adults, although no child reported the classic auras of lateral epilepsies. In total, 11% had infantile spasms (IS); post‐ictal examination provided lateralization signs in 28%. With a mean post‐surgical follow‐up duration of 5.5 years, 89% of the patients were classified as Engel Class I. Significance : Preschool children were shown to have non‐specific seizures, notably subtle events or IS. However, careful video‐EEG analysis can provide arguments for localizing the epileptogenic zone within the temporal lobe in most cases. Seizures with apnoea are characteristic of mesial temporal onset in patients with long‐term epilepsy‐associated tumours.